Comparison of Controller Tuning Techniques for A Temperature Control of STHX Process - Abirami, S; Sivagamasundari, S (International Journal of Computer Sciences and Engineering, 2018)
This paper presents the comparison of three controller tuning techniques for a Temperature Control process. The controller tuning techniques include Zeigler-Nichols (Z-N), Wang-Juang-Chan (W-J-C) and Internal Model Control based Proportional-Integral-Derivative (IMC-PID) controller. The FOPDT model for the Shell and Tube Heat Exchanger (STHX) is first obtained by first principles. The first principles model is developed using the energy balance equation of the STHX system. Then the above said tuning techniques are applied to the STHX system. The purpose of these tuning techniques is to regulate the hot water outlet temperature to a desired value by manipulating the cold water flow rate. Finally, the performances of the tuning techniques are validated with the help of performance error indices such as ISE, IAE, ITAE, and ITSE.